INTEGRASI TECHNOLOGY ACCEPTANCE MODEL DAN THEORY OF PLANNED BEHAVIOR TERHADAP INTENTION TO USE MOBILE PAYMENT (STUDI PADA PENGGUNA OVO DI SURABAYA) - YUNITA DURMAN, THEODOSIA; MUSDHOLIFAH, (Jurnal Ilmu Manajemen (JIM), 2020)
The development of technology in finance is one of the impacts of the demands of industrial revolution 4.0. One of the most highlighted developments in financial technology is the use of electronic money. Growth in the use of electronic money in Indonesia since 2015 both server-based or known as mobile payments and chip-based continues to experience a significant increase. This research uses a conceptual model of the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) and model development from previous research results. The model was empirically validated using Partial Least Square analysis using the responses gained from 100 OVO users in Surabaya. Sampling uses incidental sampling techniques. The findings of this study indicate that perceived usefulness, perceived ease of use, compatibility, security, and trust do not affect the intention to use OVO. While attitude, subjective norm, and perceived behavioral control have a positive effect on the intention to use OVO. The practical implication of this research provides strategies for mobile payment providers for technology development. Keywords: OVO users; PLS; TAM; TPB.